THE EFFECTIVENESS OF INTERNET MARKETING STRATEGY OF EMERGING BUSINESS IN INCREASING BRAND AWARENESS (CASE STUDY OF BON-BON PISANG NUGGET MANADO) - Tendean, Nessy Ingkan; Rumokoy, Farlane S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Internet users in the world increasing very rapidly and it bring so many advantages in so many aspect, especially in Business’s life, so nowadays there are a lot of business using Internet Marketing for to promote their business, and it called Internet Marketing strategy.This study aims to analyze the Effectiveness of Internet Marketing Strategy in increasing brand awareness case study of Bon-Bon Pisang Nugget Manado. This research are using qualitative research method that explore the theories from several journals, articles, books and previous research, the type of this research is descriptive research. Population in this research are all Elements that can be respondent about the Effectiveness of Internet Marketing Strategy of Emerging business in this case Bon-Bon Pisang Nugget in Increasing Brand Awareness which is all people who know or familiar about and ever bought Bon-Bon Pisang Nugget Manado. The data that gathered in this research are primary data and secondary data such as ; Interview and documentation. The result of this research is Internet Marketing strategies are effective because mostly people or customers are attracted because of the Internet Marketing tools and the suggestion is for every businesses who use Internet Marketing must operate the Internet Marketing tools well.Keywords: emerging business, internet marketing, brand awareness, brand’s reputation, brand’s recognition, brand’s priority, brand’s loyalty